2017
DOI: 10.3892/ol.2017.5813
|View full text |Cite
|
Sign up to set email alerts
|

Prodelphinidins isolated from Chinese bayberry leaves induces apoptosis via the p53-dependent signaling pathways in OVCAR-3 human ovarian cancer cells

Abstract: Abstract. Chinese bayberry leaves are rich in prodelphinidins. Since the isolation and purification of prodelphinidins is difficult, the association between the degree of prodelphinidin polymerization and their anti-carcinogenic activity remains ambiguous. The cytotoxic and apoptotic activities of prodelphinidin Chinese bayberry leaf extracts (PCBLs), oligomeric proanthocyanidins (OPAs) and polymeric proanthocyanidins (PPAs), isolated by normal-phase preparative high-performance liquid chromatography were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…To evaluate the general effect of apoptosis, cells were stained with Annexin V‐FITC and PI, and then the cell population stages were analyzed using flow cytometry. The early or late apoptotic cells were classified as quadrants, which are presented in the lower‐right (Annexin V + /PI − ) and upper‐right (Annexin V + /PI + ) quadrants (Fu, Ye, Lee, Rankin, & Chen, 2017). OJE significantly induced the early and late apoptosis stages in a concentration‐dependent manner (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the general effect of apoptosis, cells were stained with Annexin V‐FITC and PI, and then the cell population stages were analyzed using flow cytometry. The early or late apoptotic cells were classified as quadrants, which are presented in the lower‐right (Annexin V + /PI − ) and upper‐right (Annexin V + /PI + ) quadrants (Fu, Ye, Lee, Rankin, & Chen, 2017). OJE significantly induced the early and late apoptosis stages in a concentration‐dependent manner (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, OJE can effectively induce OVCAR-3 cancer cell death, even at half the concentrations of those observed in previous studies Figure 1. (Fu, Ye, Lee, Rankin, & Chen, 2017). OJE significantly induced the early and late apoptosis stages in a concentration-dependent manner (Figure 3a).…”
Section: Oje Inhibits Cell Proliferation In Ovcar-3 Cellsmentioning
confidence: 96%
“…Our previous work reported that polyphenols, prodelphinidins [ 25 ], theaflavin-3′-gallate [ 26 ] and galangin [ 27 ], induced apoptosis in ovarian cancer cells through the activation of p53 protein. To determine whether p53 is involved in CHSP-induced apoptosis of ovarian cancer cells, the expression of p53 protein was detected by Western blot.…”
Section: Discussionmentioning
confidence: 99%
“…During programmed cell death, activation of caspase-3 leads to proteolysis of DNA repair proteins and cytoskeletal proteins to alter the morphology and DNA of cells (45). Dysregulation of caspase-3 was reported in several malignancies (46)(47)(48) and overexpression of this protein was reported in HCC (49).…”
Section: Discussionmentioning
confidence: 99%